KONVERSI KEYAKINAN (STUDI PADA LIMA PENGANUT KEPERCAYAAN TOLOTANG YANG BERPINDAH KEYAKINAN MENJADI MUSLIM) - Mandjarreki, Sakaruddin; Misbach, Irwan (Jurnal Jurnalisa: Jurnal Jurusan Jurnalistik, 2019)
This study intends to explore the reality of religious conversion around the determinants of the background and the religious life of conversions after a religious conversion. This research is patterned with a phenomenological approach to reveal the subjective experience of conversion. The results showed that: The determinant factor behind the conversion to religious conversion was due to marriage. The conversion of religion that he did was not only due to the consequences of the constitutional mandate regarding the obligation to marry with the same conviction (Marriage Law No. 1 of 1974, Article 2), also because it was based on mutual feelings of mutual interest (same like). The religious life of subjects after religious conversion shows positive results in terms of dimensions; Convertible Islamic religious knowledge is increasingly increasing; The practice of converting Islamic religion in daily life is also increasing; The commitment to conversion to Islam is very strong, which is indicated by the more solid in Islam and the inclusion of several other family members in Islam through its influence.